Highlighting the value of Alzheimer’s disease-focused registries: lessons learned from cancer surveillance - Miller, Margaret C.; Bayakly, Rana; Schreurs, Bernard G.; Flicker, Kimberly J.; Adams, Swann Arp; Ingram, Lucy A.; Hardin, James W.; Lohman, Matthew; Ford, Marvella E.; McCollum, Quentin; McCrary-Quarles, Audrey; Ariyo, Oluwole; et al. (Frontiers in Aging, 2023)
Like cancer, Alzheimer's disease and related dementias (ADRD) comprise a global health burden that can benefit tremendously from the power of disease registry data. With an aging population, the incidence, treatment, and mortality from ADRD is increasing and changing rapidly. In the same way that current cancer registries work toward prevention and control, so do ADRD registries. ADRD registries maintain a comprehensive and accurate registry of ADRD within their state, provide disease prevalence estimates to enable better planning for social and medical services, identify differences in disease prevalence among demographic groups, help those who care for individuals with ADRD, and foster research into risk factors for ADRD. ADRD registries offer a unique opportunity to conduct high-impact, scientifically rigorous research efficiently. As research on and development of ADRD treatments continue to be a priority, such registries can be powerful tools for conducting observational studies of the disease. This perspectives piece examines how established cancer registries can inform ADRD registries' impact on public health surveillance, research, and intervention, and inform and engage policymakers.